2003
DOI: 10.1016/s0735-1097(03)00717-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance ofacute myocardial infarction at a very early stage

Abstract: Contrast-enhanced magnetic resonance imaging detected infarct-related signal changes as early as 1 h after AMI in humans, whereas the sensitivity of edema-related signal changes was not sufficient during this very early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…16 According to Nilsson and co-authors, 21 myocardial edema was greatest one week after the infarction and then gradually declined. Jeanette and associates 20 reported no relevant intramyocardial SI changes in T2WI within 1 hr after therapeutic septal artery embolization. These authors also found that no significant edema was detectable 7 hr after the intervention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…16 According to Nilsson and co-authors, 21 myocardial edema was greatest one week after the infarction and then gradually declined. Jeanette and associates 20 reported no relevant intramyocardial SI changes in T2WI within 1 hr after therapeutic septal artery embolization. These authors also found that no significant edema was detectable 7 hr after the intervention.…”
Section: Discussionmentioning
confidence: 97%
“…According to strong evidence, myocardial edema is predominantly intracellular early in the course of ischemic injury, and T2WI might be unable to detect bound water molecules in the case of intracellular edema. 20 The long T2 relaxation time of protons bound in free water indicates regional myocardial edema and is the primary cause of changes in T2WI signal intensity. 16 According to Nilsson and co-authors, 21 myocardial edema was greatest one week after the infarction and then gradually declined.…”
Section: Discussionmentioning
confidence: 99%
“…In studies performed following septal ablation for hypertrophic cardiomyopathy, LGE has been shown to demonstrate myocardial injury as early as 1 h after injury following the procedure [38]. There is evidence to suggest that LGE is useful in differentiating acute ischaemia from chronic irreversible myocardial injury and influencing further management of patients with ACS [39].…”
Section: S274mentioning
confidence: 99%
“…This myocardial oedema is a transient phenomenon and usually resolves at between 3 and 12 weeks. T 2 weighted imaging may help to visualise infract-related oedema without the use of contrast agent [38]. Since myocardial oedema occurs before irreversible damage, a single study using T 2 weighted imaging could be used to assess the area at risk and the eventual infarction size.…”
Section: S274mentioning
confidence: 99%
“…13,17 Also consistent with these interpretations is the reduction in T2 seen with successful treatment of myocardial edema with mannitol. 18 The increase in T2 observed with edema takes a minimum of 1 hour to be manifest in humans, 19 can be identified in dogs within 4 hours, 20 and only completely resolves some months later. 15 One question that has been raised regarding MI imaging by late-gadolinium-enhancement CMR is whether in the acute setting the gadolinium enhancement is confined to the necrotic area or whether extension occurs into the border zone of myocardial edema without necrosis, which might have increased interstitial space that could harbor gadolinium.…”
Section: Article P 1865mentioning
confidence: 99%